Ti / Al co-doped alpha-Fe2O3 photo-anode material and preparation method thereof

By doping Ti4+ and Al3+ in hematite to induce strain, the Ti/Al-Fe2O3 photoanode material was prepared, which solved the problem of low water decomposition efficiency of α-Fe2O3 photoanode and achieved efficient photoelectrochemical reaction and stable performance. .

CN119361330APending Publication Date: 2025-01-24YANGZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411567300.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The water decomposition efficiency of α-Fe2O3 photoanode is low, mainly due to its poor conductivity and short hole diffusion length, resulting in photogenerated carrier recombination loss.

Method used

By doping Ti4+ in hematite and then co-doping it with Al3+, it induces strain and improves the photoelectrochemical efficiency. The Ti/Al-Fe2O3 material is prepared by combining the hydrothermal method and the soaking method to form a nano-column structure and increase the photoelectrochemical efficiency. Large specific surface area and visible light absorption range.

Benefits of technology

The photoelectrochemical efficiency is improved, the visible light absorption range is enhanced, the preparation process is simple, no precious metal catalyst is required, the output is large, and the sample performance is stable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361330A_ABST
    Figure CN119361330A_ABST
Patent Text Reader

Abstract

The invention discloses a Ti / Al co-doped alpha-Fe2O3 photo-anode material and a preparation method thereof in the technical field of photo-anode material preparation, and the preparation method comprises the following steps: taking FeCl3. 6H2O powder, CO (NH2) 2 powder and a TiCl4 aqueous solution as raw materials, preparing a Ti-FeOOH film on FTO (Fluorine-doped Tin Oxide) through a hydrothermal reaction, then soaking the Ti-FeOOH film in an AlCl3 solution for a period of time, and annealing to obtain the Ti / Al co-doped alpha-Fe2O3 photo-anode material. The Ti / Al co-doped alpha-Fe2O3 photo-anode material provided by the invention has relatively high photoelectrochemical efficiency, and has a special nano columnar structure, so that a larger specific surface area is obtained, and the absorption range of visible light is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoanode material preparation, and in particular to a Ti / Al co-doped alpha-Fe2O3 photoanode material and a preparation method thereof. Background Art

[0002] PEC water splitting is considered a promising and low-cost method for producing hydrogen and oxygen based on semiconductor photoelectrodes. Hematite (α-Fe2O3) is considered to be one of the most promising candidate materials due to its suitable band gap (1.9 ~ 2.2 eV), non-toxicity, and high stability in aqueous electrolytes.

[0003] However, the water splitting efficiency of α-Fe2O3 is low, mainly due to its poor conductivity and short hole diffusion length (2-4 nm), which leads to recombination loss of photogenerated carriers in the α-Fe2O3 body. In order to improve its performance, several strategies have been adopted, including morphology engineering, heterostructure formation and ion doping.

[0004] Among these methods, Ti 4+ As a promising dopant, Ti can increase the carrier density of excess electrons. 4+ It has some favorable characteristics, such as its size and easy dissolution in the hematite lattice. 4+ Doping will introduce electron trapping centers, limiting the positive effect of Ti doping. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a Ti / Al co-doped α-Fe2O3 photoanode material and a preparation method thereof. The Ti / Al co-doped α-Fe2O3 photoanode material is prepared by doping Ti in hematite. 4+ , and then with Al 3 + Co-doping induces strain and improves the photoelectrochemical efficiency. The prepared Ti / Al-Fe2O3 sample has a special nano-columnar structure, so the sample obtains a larger specific surface area and enhances the absorption range of visible light.

[0006] To achieve the above object, the present invention is implemented by adopting the following technical solutions:

[0007] In one aspect, the present invention provides a method for preparing a Ti / Al co-doped α-Fe2O3 photoanode material, comprising:

[0008] Dissolve FeCl3 or its hydrate and CO(NH2)2 in deionized water, and stir to obtain a precursor solution;

[0009] Dissolve C2H6O in TiCl4 aqueous solution and stir to obtain solution A;

[0010] The solution A is mixed evenly with the precursor solution to obtain a Ti-Fe2O3 precursor solution, the fluorine-doped tin oxide glass FTO is immersed in the Ti-Fe2O3 precursor solution, and the Ti-Fe2O3 precursor solution is hydrothermally treated to obtain a Ti-FeOOH film;

[0011] AlCl3 or its hydrate is dissolved in deionized water and stirred evenly to obtain an AlCl3 aqueous solution, and a Ti-FeOOH film is immersed in the AlCl3 aqueous solution, taken out after immersion and annealed to obtain a Ti / Al co-doped α-Fe2O3 photoanode material.

[0012] Furthermore, the fluorine-doped tin oxide glass FTO is immersed in a Ti-Fe2O3 precursor solution and the Ti-Fe2O3 precursor solution is hydrothermally treated, including: transferring the Ti-Fe2O3 precursor solution to a reaction container lined with polytetrafluoroethylene, immersing the conductive part of the FTO in the Ti-Fe2O3 precursor solution, and then hydrothermally treating the Ti-Fe2O3 precursor solution, wherein the temperature of the hydrothermal treatment is 95-105°C and the time is 500-520 minutes.

[0013] Furthermore, FeCl3 or its hydrate and CO(NH2)2 are dissolved in deionized water and stirred evenly to obtain a precursor solution, wherein the molar ratio of FeCl3 or its hydrate to CO(NH2)2 is 1:0.95-1.05.

[0014] Furthermore, C2H6O is dissolved in a TiCl4 aqueous solution, wherein the mass ratio of C2H6O to the TiCl4 aqueous solution is 35-50:1.

[0015] Furthermore, the solution A is mixed evenly with the precursor solution to obtain a Ti-Fe2O3 precursor solution, wherein the mass ratio of the solution A to the precursor solution is 1:500-1000.

[0016] Furthermore, the molar concentration of the AlCl3 aqueous solution is 0.007-0.008 mmol / L.

[0017] Furthermore, the immersion is followed by taking out and annealing the film, including placing the immersed Ti-FeOOH film in a tubular furnace and annealing it at 550-600° C. for 110-120 minutes, and then heating it at 750-800° C. for 10-20 minutes.

[0018] Furthermore, after the immersion and annealing treatment, before obtaining the Ti / Al co-doped α-Fe2O3 photoanode material, a drying treatment is also included, specifically including placing the Ti-FeOOH film taken out after immersion and annealing treatment into a drying oven, and drying it at a temperature of 60-80°C for 18-24h.

[0019] Furthermore, before immersing the fluorine-doped tin oxide glass FTO in the Ti-Fe2O3 precursor solution, the fluorine-doped tin oxide glass FTO is pretreated, specifically including:

[0020] The FTO was cleaned with acetone and ethanol, respectively, and then rinsed with deionized water, and then the FTO was placed in an oven for drying;

[0021] Use a plasma cleaner to perform hydrophilic treatment on FTO.

[0022] On the other hand, the present invention provides a Ti / Al co-doped α-Fe2O3 photoanode material, which is prepared by the preparation method of the Ti / Al co-doped α-Fe2O3 photoanode material provided by the present invention.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The Ti / Al co-doped α-Fe2O3 photoanode material and the preparation method thereof provided by the present invention are obtained by doping Ti in hematite. 4+ , and then with Al 3+ Co-doping induces strain, which improves the photoelectrochemical efficiency. The prepared Ti / Al-Fe2O3 sample has a special nano-columnar structure, so the sample obtains a larger specific surface area and enhances the absorption range of visible light;

[0025] The Ti / Al co-doped α-Fe2O3 photoanode material and preparation method thereof provided by the present invention prepares high-purity Ti / Al-Fe2O3 material for the first time by combining a one-time hydrothermal method and an immersion method. The material preparation process is simple, does not require a precious metal catalyst, and has a large output. The sample has a good photocurrent density while ensuring stable performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 XRD patterns of Fe2O3, Al-Fe2O3, Ti-Fe2O3 and Ti / Al-Fe2O3 materials provided in comparative examples and embodiments of the present invention;

[0027] Figure 2 XRD (110) crystal plane magnification diagram of Fe2O3, Al-Fe2O3, Ti-Fe2O3 and Ti / Al-Fe2O3 materials provided for comparative examples and embodiments of the present invention;

[0028] Figure 3 A scanning electron microscope image of the Fe2O3 material provided as a comparative example of the present invention;

[0029] Figure 4 A scanning electron microscope image of the Al-Fe2O3 material provided as a comparative example of the present invention;

[0030] Figure 5 A scanning electron microscope image of the Ti-Fe2O3 material provided as a comparative example of the present invention;

[0031] Figure 6 A scanning electron microscope image of the Ti / Al-Fe2O3 material provided in an embodiment of the present invention;

[0032] Figure 7 The transient photocurrent response curves of Fe2O3, Al-Fe2O3, Ti-Fe2O3 and Ti / Al-Fe2O3 materials provided in the comparative examples and embodiments of the present invention;

[0033] Figure 8 LSV curves of Fe2O3, Al-Fe2O3, Ti-Fe2O3 and Ti / Al-Fe2O3 materials provided in comparative examples and embodiments of the present invention;

[0034] Fig. 9 UV-visible absorption diagrams of Fe2O3, Al-Fe2O3, Ti-Fe2O3 and Ti / Al-Fe2O3 materials provided in comparative examples and embodiments of the present invention;

[0035] Fig.10 Mott-Schottky curves of Fe2O3, Al-Fe2O3, Ti-Fe2O3 and Ti / Al-Fe2O3 materials provided in comparative examples and embodiments of the present invention;

[0036] Fig.11 Impedance curves of Fe2O3, Al-Fe2O3, Ti-Fe2O3 and Ti / Al-Fe2O3 materials provided in comparative examples and embodiments of the present invention;

[0037] Fig.12 CV curves of Fe2O3, Al-Fe2O3, Ti-Fe2O3 and Ti / Al-Fe2O3 materials provided in comparative examples and embodiments of the present invention;

[0038] Fig.13 The XPS curve diagram of the Fe2O3 material provided for the comparative example of the present invention;

[0039] Fig.14 XPS curve diagram of Al-Fe2O3 material provided for comparative example of the present invention;

[0040] Fig.15 XPS curve diagram of Ti-Fe2O3 material provided for comparative example of the present invention;

[0041] Fig.16 This is an XPS graph of the Ti / Al-Fe2O3 material provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0042] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0043] The specifications of the substrate FTO glass used in the embodiments of the present invention are all 1cm×2cm, and all are pretreated. The pretreatment method is specifically as follows: cleaning with acetone and ethanol, then rinsing with deionized water, and placing it in an oven for drying; using a plasma cleaner to perform a hydrophilic treatment to enhance the contact between its surface and the solution, which is beneficial to the synthesis of the sample in an aqueous solution; covering one end of the conductive side of the FTO substrate (1cm×1cm) and the entire non-conductive side to ensure that the material grows only on one end of the conductive side of the FTO substrate.

[0044] Example 1

[0045] This embodiment provides a Ti / Al co-doped α-Fe2O3 photoanode material, denoted as Ti / Al-Fe2O3 material, and a preparation method thereof, including:

[0046] 1) Dissolve 3 mmol FeCl3·6H2O and 3.15 mmol CO(NH2)2 in 20 ml deionized water solution and stir for 5 minutes to form a uniform precursor solution;

[0047] 2) Dissolve 10 ml of C2H6O in 300 μl of TiCl4 aqueous solution and stir for 5 minutes, which is called solution A.

[0048] 3) Dissolve 40 μl of solution A in the precursor solution prepared in step 1), stir for 5 minutes to obtain a Ti-Fe2O3 precursor solution, transfer the Ti-Fe2O3 precursor solution and the pretreated FTO substrate together into an autoclave lined with polytetrafluoroethylene, and then place it in a preset air drying oven at 100° C. for drying for 500 minutes to obtain a Ti-FeOOH film, wherein the conductive part of the pretreated FTO substrate is immersed in the Ti-Fe2O3 precursor solution;

[0049] 4) Take 0.036g of anhydrous AlCl3 and dissolve it in 20ml of deionized water solution. After stirring for 5 minutes, soak the Ti-FeOOH film in it for two minutes, and then put it into a tube furnace for two-step annealing treatment: first annealing at 550℃ for 2 hours, followed by a short heating at 750℃ for 15 minutes;

[0050] 5) Take out the FTO film sample and put it into a drying oven and dry it at 60°C for 24 hours to obtain the Ti / Al-Fe2O3 photoanode material.

[0051] Comparative Example 1

[0052] This comparative example provides a Fe2O3 material, and the preparation method is as follows:

[0053] 1) Dissolve 3 mmol FeCl3·6H2O and 3.15 mmol CO(NH2)2 in 20 ml deionized water solution and stir for 5 minutes to form a uniform precursor solution;

[0054] 2) placing the precursor solution prepared in step 1) and the pretreated FTO substrate together in a 40 mL polytetrafluoroethylene-lined autoclave, and then placing in a preset 100° C. air drying oven for 500 minutes to obtain a FeOOH base film;

[0055] 3) The FeOOH-based film was collected, annealed at 550°C for 2 hours, then annealed at 750°C for 15 minutes, and finally dried in vacuum at 60°C for 24 hours to obtain Fe2O3.

[0056] Comparative Example 2

[0057] This comparative example provides an Al-doped α-Fe2O3 material, referred to as Al-Fe2O3 material, the preparation method of which includes:

[0058] 1) Weigh 0.007455mmol / L AlCl3 and dissolve it in 20ml deionized water solution, and stir for 5 minutes to obtain AlCl3 aqueous solution;

[0059] 2) The FeOOH-based film was immersed in an AlCl3 aqueous solution for 2 minutes, then taken out and placed in a tube furnace, first annealed at 550°C for 2 hours, and then heated at 750°C for 15 minutes to obtain an Al-Fe2O3 material.

[0060] The FeOOH base film is prepared in the same manner as the FeOOH base film in Comparative Example 1.

[0061] Comparative Example 3

[0062] This comparative example provides a Ti-doped α-Fe2O3 material, referred to as Ti-Fe2O3 material, the preparation method of which includes:

[0063] 1) Dissolve 3 mmol FeCl3·6H2O and 3.15 mmol CO(NH2)2 in 20 ml deionized water solution and stir for 5 minutes to form a uniform precursor solution;

[0064] 2) Dissolve 10 ml of C2H6O in 300 μl of TiCl4 aqueous solution and stir for 5 minutes, which is called solution A.

[0065] 3) Take 40 μl of solution A and add it to the precursor solution prepared in step 1), stir for 5 minutes to obtain a Ti-Fe2O3 precursor solution, put the Ti-Fe2O3 precursor solution and the pretreated FTO substrate into a 40 mL polytetrafluoroethylene-lined autoclave, and then put it into a preset 100°C air drying oven for drying for 500 minutes to obtain a Ti-FeOOH film;

[0066] 4) The Ti-FeOOH film was collected, annealed at 550°C for 2 hours, then annealed at 750°C for 15 minutes, and finally vacuum dried at 60°C for 24 hours to obtain a Ti-Fe2O3 material.

[0067] Figure 1 The XRD diagrams of Fe2O3, Al-Fe2O3, Ti-Fe2O3 prepared in Comparative Examples 1-3 and Ti / Al-Fe2O3 prepared in Example 1 are shown in FIG. Figure 2 The XRD (110) crystal plane magnification diagram of Fe2O3, Al-Fe2O3, Ti-Fe2O3 prepared in Comparative Examples 1-3 and Ti / Al-Fe2O3 prepared in Example 1. Figure 1 It can be found that except for the peak of FTO substrate, no other impurity peaks were detected, indicating that we have prepared relatively uniform Fe2O3. In addition, single element doping and co-doping have no effect on the crystal structure of undoped α-Fe2O3 film. 4+ (ionic radius 0.68Å) slightly larger than Fe 3+ (ion radius 0.64Å), the addition of Ti4+ into Fe2O3 will cause the Fe2O3 lattice to expand, and the (110) peak with the highest intensity will shift slightly to a higher angle. Compared with Al-Fe2O3, the (110) crystal plane of Ti / Al-Fe2O3 shifts to a lower angle, which may be due to the fact that Al 3+ (ionic radius 0.50Å) is significantly smaller than Fe 3+ (ionic radius 0.64Å) neutralizes Ti 4+ The effect of dopants, indicating that a small amount of Ti is substituted in the lattice 4+The concentration can relieve strain through smaller volume distortion.

[0068] Figures 3 to 6 They are SEM images of Fe2O3, Al-Fe2O3, Ti-Fe2O3 prepared in Comparative Examples 1-3 and Ti / Al-Fe2O3 prepared in Example 1. Figure 3 The SEM image of the pure Fe2O3 film shows an array structure with many irregular morphologies, with an average diameter of about 100nm. Figure 5 As shown in the figure, it has a similar morphology to the pure Fe2O3 film, with little change in size. After the introduction of Al element, its morphology is as follows Figure 4 As shown in the figure, it has become a more dense nano-columnar structure, which is quite different from the original morphology, and the size has been significantly reduced to about 60nm. After co-doping with Ti and Al elements, its morphology is as follows Figure 6 As shown, they are grown on the FTO substrate in the form of a higher density array, and the average size is reduced from the original 100nm to 50nm.

[0069] Figure 7 The transient photocurrent response curves of Fe2O3, Al-Fe2O3, Ti-Fe2O3 prepared in Comparative Examples 1-3 and Ti / Al-Fe2O3 prepared in Example 1 are shown in FIG. Figure 7 As shown, the photocurrents of Fe2O3, Al-Fe2O3, Ti-Fe2O3 and Ti / Al-Fe2O3 are 50μA, 520μA, 220μA and 340μA respectively. Compared with pure Fe2O3, the photocurrents of Al-Fe2O3, Ti-Fe2O3 and Ti / Al-Fe2O3 increased by 10.4, 4.4 and 6.8 times respectively, which indicates that both single element doping and co-doping play a role in improving the photocurrent.

[0070] Figure 8 The LSV curves of Fe2O3, Al-Fe2O3, Ti-Fe2O3 obtained in Comparative Examples 1-3 and Ti / Al-Fe2O3 obtained in Example 1 are shown in FIG. Figure 8 As shown in Figure 2, the photocurrent density of Al-Fe2O3 at 1.23 VRHE reached 1.05 mA / cm 2 , which is 5.8 times that of pure Fe2O3. The photocurrent density of Ti-Fe2O3 at 1.23VRHE reaches 1.75mA / cm 2 , which is 9.7 times that of pure Fe2O3. The photocurrent density of Ti / Al-Fe2O3 at 1.23VRHE reaches 2.23mA / cm 2 , which is 12.3 times that of pure Fe2O3, and its turn-on voltage has a significant cathode shift of about 260mV.

[0071] Fig. 9 The UV-visible absorption curves of Fe2O3, Al-Fe2O3, Ti-Fe2O3 prepared in Comparative Examples 1-3 and Ti / Al-Fe2O3 prepared in Example 1 are shown. Compared with the original Fe2O3 film, the light absorption of Al-doped Fe2O3 film, Ti-doped Fe2O3 film and Ti and Al co-doped Fe2O3 film at 200-600nm is significantly increased. The foreign dopant in the α-Fe2O3 lattice is believed to play an important role in increasing the optical absorption, especially the absorbance of Ti-Al-Fe2O3 film is significantly increased compared with the pure Fe2O3 film.

[0072] Fig.10 The Mott-Schottky curves of Fe2O3, Al-Fe2O3, Ti-Fe2O3 obtained in Comparative Examples 1-3 and Ti / Al-Fe2O3 obtained in Example 1 are shown in FIG. Fig.10 As shown in the figure, the Mott-Schottky MS curves of the four samples all have a positive slope, which is a characteristic of n-type semiconductors. Their flat band potential values ​​relative to RHE are 0.81, 0.84, 0.96, and 1.04, respectively, from which their donor densities can be calculated to be Fe2O3:2.23*10 18 cm -3 ;Al-Fe2O 3: 3.01*10 18 cm -3 ;Ti-Fe2O3:1.13*10 19 cm -3 ;Ti / Al-Fe2O 3: 4.86*10 18 cm -3 The donor density of Ti-doped Fe2O3 film is the largest among all photoanodes, about 5.1 times that of pure Fe2O3, and the donor density of Fe2O3 film co-doped with Ti and Al is about 2.2 times that of pure Fe2O3. The greater the donor density, the more obvious the band bending between the photoanode and electrolyte interface, and the greater the electric field on the space charge layer.

[0073] Fig.11 The impedance curves of Fe2O3, Al-Fe2O3, Ti-Fe2O3 obtained in Comparative Examples 1-3 and Ti / Al-Fe2O3 obtained in Example 1 are shown. The semicircle diameter of the impedance EIS curve is related to the impedance. The smaller the diameter, the smaller the impedance. It can be seen that the resistance values ​​of Al-Fe2O3, Ti-Fe2O3 and Ti / Al-Fe2O3 are all smaller than that of Fe2O3. This is consistent with the test results of MS. Ion doping brings about an increase in donor concentration, increases the conductivity of the Fe2O3 photoanode, and enhances the separation efficiency of carriers.

[0074] like Fig.12 The CV curves of Fe2O3, Al-Fe2O3, Ti-Fe2O3 prepared in Comparative Examples 1-3 and Ti / Al-Fe2O3 prepared in Example 1. The double layer capacitance values ​​of Fe2O3, Ti-Fe2O3 and Ti / Al-Fe2O3 are 29.86 μF / cm 2 、56.44μF / cm 2 and 69.52μF / cm 2 Compared with pure Fe2O3, the Cdl values ​​of Ti-Fe2O3 and Ti / Al-Fe2O3 increased by 1.89 times and 2.33 times, respectively. The above results show that Ti and Al provide more active sites in a very small amount during doping, increase the electrochemical active surface area, and effectively promote the surface water oxidation performance.

[0075] Figure 13-16 The XPS curves of Fe2O3, Al-Fe2O3, Ti-Fe2O3 obtained in Comparative Examples 1-3 and Ti / Al-Fe2O3 obtained in Example 1 are shown respectively. Figure 13-16 As shown, the Fe2O3 electrode has 2p at 710.60eV and 724.12eV respectively. 3 / 2 and 2p 1 / 2 Peak, indicating Fe 2p The presence of O in Al-Fe2O3 v The intensity is much higher than that of pure Fe2O3, indicating that there are more oxygen vacancies in Al-Fe2O3. However, the more oxygen vacancies, the better. The intensity of oxygen vacancies in co-doped Fe2O3 is weaker than that of Al-doped peaks, indicating that the fewer defects in the material, the less charge recombination, and these phenomena are conducive to photochemical catalytic water oxidation. In addition to the peaks of Fe and O, the peaks of Al and Ti can be identified from the XPS spectrum, which means that Al and Ti atoms have been doped into Fe2O3.

[0076] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the enlightenment of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present invention and the claims, which all fall within the protection of the present invention.

Claims

1. A method for preparing a Ti / Al co-doped α-Fe2O3 photoanode material, characterized in that: include: Dissolve FeCl3 or its hydrate and CO(NH2)2 in deionized water, and stir to obtain a precursor solution; Dissolve C2H6O in TiCl4 aqueous solution and stir to obtain solution A; The solution A is mixed evenly with the precursor solution to obtain a Ti-Fe2O3 precursor solution, the fluorine-doped tin oxide glass FTO is immersed in the Ti-Fe2O3 precursor solution, and the Ti-Fe2O3 precursor solution is hydrothermally treated to obtain a Ti-FeOOH film; AlCl3 or its hydrate is dissolved in deionized water and stirred evenly to obtain an AlCl3 aqueous solution, and a Ti-FeOOH film is immersed in the AlCl3 aqueous solution, taken out after immersion and annealed to obtain a Ti / Al co-doped α-Fe2O3 photoanode material.

2. The method for preparing the Ti / Al co-doped α-Fe2O3 photoanode material according to claim 1, characterized in that: The method of immersing the fluorine-doped tin oxide glass FTO in a Ti-Fe2O3 precursor solution and performing a hydrothermal treatment on the Ti-Fe2O3 precursor solution comprises: transferring the Ti-Fe2O3 precursor solution to a reaction container lined with polytetrafluoroethylene, immersing the conductive part of the FTO in the Ti-Fe2O3 precursor solution, and then performing a hydrothermal treatment on the Ti-Fe2O3 precursor solution, wherein the temperature of the hydrothermal treatment is 95-105° C. and the time is 500-520 minutes.

3. The method for preparing the Ti / Al co-doped α-Fe2O3 photoanode material according to claim 1, characterized in that: The FeCl3 or its hydrate and CO(NH2)2 are dissolved in deionized water and stirred to obtain a precursor solution, wherein the molar ratio of FeCl3 or its hydrate to CO(NH2)2 is 1:0.95-1.

05.

4. The method for preparing the Ti / Al co-doped α-Fe2O3 photoanode material according to claim 1, characterized in that: The C2H6O is dissolved in a TiCl4 aqueous solution, wherein the mass ratio of C2H6O to the TiCl4 aqueous solution is 35-50:

1.

5. The method for preparing the Ti / Al co-doped α-Fe2O3 photoanode material according to claim 1, characterized in that: The solution A is mixed evenly with the precursor solution to obtain a Ti-Fe2O3 precursor solution, wherein the mass ratio of the solution A to the precursor solution is 1:500-1000.

6. The method for preparing the Ti / Al co-doped α-Fe2O3 photoanode material according to claim 1, characterized in that: The molar concentration of the AlCl3 aqueous solution is 0.007-0.008 mmol / L.

7. The method for preparing the Ti / Al co-doped α-Fe2O3 photoanode material according to claim 1, characterized in that: The method of taking out the film after immersion and performing annealing treatment comprises placing the immersed Ti-FeOOH film in a tubular furnace and annealing it at 550-600° C. for 110-120 minutes, and then heating it at 750-800° C. for 10-20 minutes.

8. The method for preparing the Ti / Al co-doped α-Fe2O3 photoanode material according to claim 1, characterized in that: After the immersion and annealing treatment, before obtaining the Ti / Al co-doped α-Fe2O3 photoanode material, a drying treatment is also included, specifically including placing the Ti-FeOOH film taken out after immersion and annealing treatment into a drying oven and drying it at a temperature of 60-80°C for 18-24h.

9. The method for preparing the Ti / Al co-doped α-Fe2O3 photoanode material according to claim 1, characterized in that: Before immersing the fluorine-doped tin oxide glass FTO in the Ti-Fe2O3 precursor solution, the fluorine-doped tin oxide glass FTO is also pretreated, specifically including: The FTO was cleaned with acetone and ethanol, respectively, and then rinsed with deionized water, and then the FTO was placed in an oven for drying; Use a plasma cleaner to perform hydrophilic treatment on FTO.

10. A Ti / Al co-doped α-Fe2O3 photoanode material, characterized in that: Prepared by the method described in any one of claims 1 to 9.

Citation Information

Cited By

  • Titanium fluoride doped iron oxide photo-anode and preparation method and application thereof

    CN120736803A